PENGARUH LOCUS OF CONTROL DAN SELF EFFICACY TERHADAP PERILAKU ETIS (Studi Kasus Mahasiswa Akuntansi Universitas Pekalongan) - Fangela Myas Sari (Universitas Teuku Umar, 2023)
This study aims to see the influence of accounting students who behave ethically. This research is reviewed from locus of control, self efficacy. The subjects of this study were accounting students at the Pekalongan University. While the object of research is the ethical behavior of accounting students at Pekalongan University. The data in the study were collected using a questionnaire,for the sampling method using convenience sampling method.The results of this study indicate that locus of control has a positive and significant effect on ethical behavior, self-efficacy has a positive and significant effect on ethical behavior.Keywords : Effect of Locus Of Control, Self Efficacy, Student Ethical Behavior.